Extreme re-listening: Songs people love . . . and continue to love. (March 2019) - Conrad, Frederick; Corey, Jason; Goldstein, Samantha; Ostrow, Joseph; Sadowsky, Michael
Despite the lack of surprise each time they listen to their favorite song, people re-listen to these songs many times. We explored "extreme re-listening" by conducting a survey about the song to which participants were "listening most often these days." We questioned participants about their listening experience, e.g., the deepness of their connection to the song, which aspects of the song draw them back, how much of the song they were able to hear in their heads, and how (in their own words) the song made them feel, which we classified as "happy, " "calm, " and "bittersweet." More participants whose favorite song made them feel happy reported being drawn back because of its beat/rhythm. Participants whose favorite song made them feel bittersweet reported having a deeper connection to the song than those whose favorite song evoked other feelings. These patterns held irrespective of musical training. Finally, we found that the more times they listened to their favorite song, the more of the song listeners could hear internally. People's affection for songs to which they voluntarily listen at high rates appears not to wane as it does for songs to which their exposure is ambient as is the case with the hit parade.